Convergence Theorems of Iterative Schemes For Nonexpansive Mappings - Ali Hadi, Inaam Mohammed; Salman Abd, Dr. salwa (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
In this paper, we give a type of iterative scheme for sequence of nonexpansive mappings and we study the strongly convergence of these schemes in real Hilbert space to common fixed point which is also a solution of a variational inequality. Also there are some consequent of this results in convex analysis